Determination of allelopathic potential in mahogany (Swietenia macrophylla King) leaf litter using sandwich method - Arnia Sari Mukaromah; Yekti Asih Purwestri; Yoshiharu Fujii (Universitas Gadjah Mada, 2016)
The sandwich method is a reliable screening bioassay that can be utilized to investigate allelopathic activity of leaf litter leachates. Screening the allelopathic potential of mahogany (Swietenia macrophylla King) leaf litter in plant–plant interaction using the sandwich bioassay method has not been reported. The research objectives were to determine and categorize allelopathic potential of S. macrophylla leaf litter using the sandwich bioassay method, and to determine specific activity (EC550). S. macrophylla leaf litter. The results showed that S. macrophylla leaf litter exhibited strong allelopathic activity when compared with 46 leaf litter species and was included in the top ten of allelopathic leaf litter species. Increasing S. macrophylla leaf litter concentration was concomitant with inhibition of radicle lettuce seedling growth compared with the control. According to the linear regression analysis, the effective concentration (EC50) of S. macrophylla was estimated to be 3.25 mg D.W. eq. mL-1 and was considered to have strong growth-inhibitory activity on lettuce radicle elongation. The results suggest the possibility of allelopathic potential of leaf litter in plant–plant interaction under S. macrophylla trees.